Collagen-disrupting attIL12 TIL therapy boosts deep T cell infiltration via dual signaling activation and CCKAR reduction in sarcomas - Jiemiao Hu; Harjeet Singh; Yining Jin; Wendong Zhang; Jian Wang; Xueqing Xia; Neeta Somaiah; Richard Gorlick; Shulin Li (Proceedings of the National Academy of Sciences, 2025)
Tumor-targeted T cell therapies of various types have been booming, but T cell therapy is limited by its inability to penetrate the collagen barrier surrounding tumors. The destruction of tumor collagen is significant because collagen both suppresses T cells and contributes to the formation of the extracellular matrix. Our previously reported cell-surface vimentin (CSV)–targeted and membrane-anchored interleukin 12-armed (attIL12) T cells can reduce collagen production by killing cancer-associated fibroblasts, but fail to reduce collagen expression by tumor cells, resulting in resistance to attIL12-T cell treatment. In this study, we found that CCKAR directly boosts collagen production by tumor cells in vitro and in vivo. attIL12-modified tumor-infiltrating lymphocytes (TILs) disabled collagen production by CCKAR-high autologous tumor cells in vitro and sarcoma patient-derived xenografts (PDXs) in vivo. This disruption of collagen production by tumor cells by attIL12-TILs overcomes resistance to attIL12-T cell treatment and required a simultaneous interaction between the CSV on autologous tumor cells, which is targeted by attIL12, and human leukocyte antigen-T cell receptor on attIL12-TILs; When either interaction was abrogated, collagen production and CCKAR expression were not shut down. Mechanistically, the interaction between attIL12-TILs and autologous tumor cells induced interferon gamma production synergistically, which in combination with CCKAR downregulation reduced collagen expression through suppression of both transforminggrowth factor beta-stimulated SMAD activation and CCKAR-AKT signaling. Diminishing collagen expression from tumor cells significantly increased T cell infiltration and improved tumor growth inhibition in PDX sarcomas. Thus, this attIL12-TIL therapy holds great clinical potential for boosting T cell infiltration in high-grade, collagen-rich tumors.